Effectiveness of Quizizz Gamification Mastery Peak Model on Critical Thinking and Collaboration Skills of Junior High School Students - Akhir Andika Aritonang; Irvan Irvan (JMEA : Journal of Mathematics Education and Application, 2025)
This study aims to examine the effectiveness of implementing Quizizz gamification based on the Mastery Peak model in improving students' critical thinking and collaboration skills at SMP IT Madani. A quasi-experimental method with a pretest–posttest control group design was used. The sample consisted of 60 eighth-grade students, divided into two groups: an experimental group (using Mastery Peak Quizizz) and a control group (conventional learning), each consisting of 30 students. The instruments used included descriptive tests to measure critical thinking and a Likert scale questionnaire to assess collaboration skills. The results showed that the experimental group improved their critical thinking posttest scores from 63.67 to 84.50, with a normalized gain (N-Gain) of 0.56 (medium–high category), while the control group improved from 65.67 to 75.67 (N-Gain = 0.30). This difference was statistically significant (p = 0.0005). In terms of collaboration, the experimental group's scores increased from 60.87 to 88.53 (N-Gain = 0.71), while the control group increased from 61.93 to 74.27 (N-Gain = 0.37), also showing a significant difference. The most improved dimensions were open communication and joint decision-making. These findings provide practical insights that Mastery Peak-based gamification is effective not only in enhancing cognitive achievement but also in fostering social interaction and teamwork. Therefore, this strategy is recommended as a relevant and transformative instructional approach for developing 21st-century skills.